Political Elites’ Corruption, Political Stability and Economic Growth in Nigeria: Bound Testing Approach: Array - Kyarem, Richard; Sani, Ibrahim Abubakar; Oyolola, Feyisayo; Lawal, Olasunkanmi (Acta Universitatis Danubius. Œconomica, 2020)
This paper investigated the impact of political elites’ corruption and political stability on economic growth in Nigeria using ARDL bound test approach. The study adopts annual time series data for the period of 1996-2017. The stationarity properties of the variables were tested using Augmented Dickey Fuller (ADF) and Phillips-Perron (PP) tests. Result from the bound test reveals that corruption exact a negative and significant impact on economic growth both in the short and long run, while political stability exact a positive and significant impact on economic growth in the short run and an insignificant impact in the long run. This finding reveals that political stability which includes stability in government, absence of internal, external and ethnic conflict/tension promote economic growth in Nigeria in the short run while corruption contributes to the Nigeria’s economic growth by reducing cumbersome bureaucratic control.